I have an answer for this question, but I'm not very confident with it:

$\left | 1-e^{i\theta } \right |^{2}$ i.e. find the square of the modulus of 1-$e^{i\theta }$

$e^{i\theta } = R(cos\theta +isin\theta )$, R=1

= $cos\theta +isin\theta$

In cartesian form:

$a = Rcos\theta \Rightarrow cos\theta$

$b = Rsin\theta \Rightarrow sin\theta$

$\therefore 1-e^{i\Theta } = 1-cos\theta-isin\theta$

$\Rightarrow \left | 1-e^i\theta \right | = \left | 1-cos\theta-isin\theta \right |$

Where the real part, a, = $1-cos\theta$ and the imaginary, b, = $-sin\theta$

The modulus of a complex number being $\sqrt{a^{2} +b^{2}}$

$\therefore \left | 1-cos\theta-isin\theta \right | = \sqrt{(1-cos\theta)^{2} + (-sin\theta)^{2}}$

$\Rightarrow \left | 1-cos\theta-isin\theta \right |^{2} = (1-cos\theta)^{2} + (-sin\theta)^{2} \Rightarrow 1-2cos\theta +cos^{2}\theta +sin^{2}\theta \Rightarrow (\because cos^{2}\theta +sin^{2}\theta = 1) = 2-2cos\theta$

Is this correct? Or is my approach incorrect? Thanks in advance for any feedback/help :)

  • $\begingroup$ It is correct but extremely long. I think anyone dealing with this could be dispensed with all those explanations, and then you could simply write:$$|1-\cos\theta-i\sin\theta|^2=(1-\cos\theta)^2+\sin^2\theta=2(1-\cos\theta)$$ $\endgroup$ – DonAntonio May 13 '17 at 9:20

Your argument is lengthy, but sound.

If just the square of the modulus is needed, you can consider that $|z|^2=z\bar{z}$, so $$ |1-e^{i\theta}|^2=(1-e^{i\theta})(1-e^{-i\theta})= 1-(e^{i\theta}+e^{-i\theta})+1=2-2\cos\theta $$

If also the argument is needed, the trick with $1-e^{i\theta}$ (but also $1+e^{i\theta}$) is to set $$ \theta=2\alpha $$ and rewrite $$ 1-e^{i\theta}=1-e^{2i\alpha}= -e^{i\alpha}(e^{i\alpha}-e^{-i\alpha})=-2i(\sin\alpha)e^{i\alpha} $$ Since $0\le\theta<2\pi$, we have $0\le\alpha<\pi$, so $\sin\alpha\ge0$. Hence the modulus is $2\sin\alpha$ and, from $-i=e^{3i\pi/2}$, the argument is $$ \alpha+\frac{3\pi}{2} $$ (up to an integer multiple of $2\pi$).

Thus the square of the modulus is $$ 4\sin^2\alpha=4\sin^2\frac{\theta}{2}=4\frac{1-\cos\theta}{2}= 2(1-\cos\theta) $$

  • $\begingroup$ Thanks for your response! That makes a lot of sense too. I love how there's always several ways to solve a question! $\endgroup$ – Skylineblue May 14 '17 at 1:46


Now $2-2\cos\theta=4\sin^2\dfrac\theta2$ using $\cos2A=1-2\sin^2A$

Finally for real $u,\sqrt{u^2}=|u|=\begin{cases} +u &\mbox{if } u\ge0 \\ -u & \mbox{if } u<0 \end{cases} $



Alternatively, $$1-\cos\theta-i\sin\theta=2\sin^2\dfrac\theta2--2i\cos\dfrac\theta2\sin\dfrac\theta2=-2i\sin\dfrac\theta2\left(\cos\dfrac\theta2+i\sin\dfrac\theta2\right)$$

  • $\begingroup$ I actually got to the 4sin^2(theta/2), but I didn't add it to the post as I figured the two were equivalent so if one was correct the other is as well. I don't quite understand why you wrote the lines afterwards about u, (u^2)^1/2 = |u| etc. Is this necessary? i.e. is simply writing 4sin^2(theta/2) the correct answer? $\endgroup$ – Skylineblue May 13 '17 at 9:20
  • $\begingroup$ @Skylineblue, $$4\sin^2\dfrac\theta2$$ is actually the square of the modulus right? $\endgroup$ – lab bhattacharjee May 13 '17 at 9:23
  • $\begingroup$ Well, I wrote $\therefore \left | 1-cos\theta-isin\theta \right | = \sqrt{(1-cos\theta)^{2} + (-sin\theta)^{2}}$, then the square of the modulus would get rid of the square root, and then follows on to what I get in the end. I'm also a little confused with your response. :S $\endgroup$ – Skylineblue May 13 '17 at 9:26
  • $\begingroup$ @Skylineblue, How could you get rid of the square root? Do you mean $$\sqrt{a^2+b^2}=a^2+b^2$$ $\endgroup$ – lab bhattacharjee May 13 '17 at 9:29

Just take $2$ common from the final result and apply the formulae $$1-\cos\theta=2\sin^2\frac{\theta}{2}$$ Your answer will be simplified.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.